Use of a tablet-based application for clinical handover and data collection. (2nd July 2020) - Downes, Michael A.; Page, Colin B.; Berling, Ingrid; Whyte, Ian M.; Isbister, Geoffrey K.
Abstract: Context: Inpatient toxicology services undertake remote as well as inpatient management of poisoned patients. The aim of this study is to describe the introduction of a tablet-based electronic data collection tool allowing data to be captured on inpatient and remote consultations. Methods: Retrospective review of all cases entered in the database from 1 March 2014 to 28 February 2016. Data collected included demographics (age, sex), clinical details (exposure category), presentation facility and disposition. Results: The database included 3616 cases: 59 (1.6%) were excluded due to inadequate details, 122 (3.4%) had no electronic medical record available, 1985 (54.9%) presented to the inpatient unit facility and 1450 (40.1%) were external consultations. Of these 1450, 223 (6.2%) were paediatric (aged less than 12 years), 395 (10.9%) adolescent (12–17 years) and 832 (23.0%) adults (18 years and over). The proportion of paediatric cases (median age 2 y; 45.7% females) with pharmaceutical ingestions was 122 (54.7%; 95% confidence intervals (CIs): 48.2–61.1) compared with 345 (87.3%; 95% CI: 83.7–90.3) in adolescents (median age 15 y; 79.5% females). Of the adult presentations, 659 (18.2%) were metropolitan/regional facility presentations and 173 (4.8%) rural facilities with 125 (3.4%) adults subsequently transferred to the inpatient facility. Median age was 38 years (interquartile range (IQR) 35–52) with 338 (51.4%) females in the metropolitan group and 37 years (IQR 26–48) with 51 (30.5%) females in the rural group. There were more bites and stings in the rural group, 41 (23.7%; 95% CI: 18.0–30.6) versus 54 (8.2%; 95% CI: 6.3–10.5), more recreational substance exposures 27 (15.6%; 95% CI: 11.0–21.8) versus 40 (6.1%; 95% CI: 4.5–8.2) and less pharmaceutical exposures 93 (53.8%; 95% CI: 46.3–61.0) versus 462 (70.1%; 95% CI: 66.5–73.5). Conclusions: The tablet based database provided useful information on populations of poisoned patients not accessible previously. It demonstrated important differences in the types of patients presenting to rural versus metropolitan hospitals